Diagnostic workup of endocrine dysfunction in recurrent pregnancy loss: a cross-sectional study in Northeast China - Zhang, Liyang; Du, Yushu; Zhou, Jingshuang; Li, Jiapo; Shen, Hongfei; Liu, Yilin; Liu, Chuanyang; Qiao, Chong (Frontiers in Endocrinology, 2023)
Objective：To evaluate the prevalence of abnormal endocrine dysfunction for recurrent pregnancy loss (RPL) amongst patients with two versus three or more pregnancy losses.This cross-sectional study retrospectively collected pre-pregnancy data of 537 women diagnosed with RPL in Shengjing Hospital of China Medical University from 2017 to 2022 , including the baseline data of patients and the test results of endocrine factors. Several endocrine dysfunction included in this study were: thyroid dysfunction, obesity, hyperprolactinemia, polycystic ovary syndrome and blood glucose abnormality. Furthermore, vitamin D level were collected to study its relationship with endocrine dysfunction. Finally, we subdivided the patients according to the number of previous pregnancy loss and compared the prevalence of endocrine dysfunction between subgroups.Results: Among 537 RPL patients, 278 (51.8%) patients had abnormal endocrine test results. The highest incidence of endocrine dysfunction was thyroid dysfunction (24.39%, 131/537), followed by hyperprolactinemia (17.34%, 85/490), obesity (10.8%, 58/537), polycystic ovary syndrome (10.50%, 56/533), and abnormal blood glucose (5.29%, 27/510). Only 2.47%(13/527) of patients have vitamin D level that reach the standard. After subdividing the population according to the number of pregnancy loss, we did not find that the incidence of endocrine dysfunction (P=0.813), thyroid dysfunction (P=0.905), hyperprolactinemia (P=0.265), polycystic ovary syndrome (P=0.638), blood glucose abnormality (P=0.616)and vitamin D deficiency (P=0.908) were different among patients with two versus three or more pregnancy losses. However,obesity (P=0.003) was found more frequently observed in patients with more times of pregnancy loss.The prevalence of endocrine dysfunction in RPL population is high. There is no difference in the prevalence of endocrine dysfunction, except for obesity, among patients with two or more pregnancy losses, which may suggest investigations of endocrine dysfunction when patients have two pregnancy losses.